Pedagogy in performance: An approach to theatre teaching in elementary school - Martins, Pedro Haddad [UNESP] (Univ Estado Santa Catarina-udesc, 2019)
This article seeks to contextualize, articulating theory and practice in the classroom, what would be a pedagogy in performance - a theater teaching that affirms itself as contemporary practice from the performative theater, and does not forget elements of its tradition. Here, the performativity of the child is taken as poetic material for theatrical construction, and effectives experience as a practice of elaboration of knowledge in art. The research, conducted from the work with 38 sixth grade theater classes from 2012 to 2017, seeks, through the report of experiences, a possible answer to the question: what approaches to theater teaching/learning are potent today?
Keywords: Theater pedagogy; theater teaching; performative theater; performativity; theater-education